Patterns of Muscle Activity Measurement in Male Students With Forward Head Posture Compared to Healthy Peers During Running - Amirali Jafarnezhadgero; Saeideh HeshmatiZadeh; Somaye Salahi-Movasagh; Farzaneh Saki (Biyumikānīk-i varzishī, 2019)
Objective The aim of this study was to evaluate the muscular activity timing during running in male children with forward head posture compared to healthy control ones. Methods 12 healthy male children with forward head posture (age: 11.7±1.4 years; height: 149.7±6.2 cm; Mass: 38.0±4.7 kg) and 16 healthy male children (age: 11.8±1.5 years; height: 148.2±6.6 cm; mass: 39.6±0.4 kg) were volunteered to participate in this study. The timing of muscular activity for erector spinae (cervical region), sternocleidomastoid, serratus anterior, upper and lower trapezius muscles of both right and left sides were evaluated during barefoot running. Muscular activity was recorded with a 16-chanels electromyography system. Independent sample t-test was used for statistical analysis. Results Finding did not demonstrate any significant differences in onset and offset of muscular activity during walking between both groups (P>0.05). The time duration of right erector spinae muscle in the healthy group was greater than that forward head group about 41 ms (P=0.024). Also, the time duration of left sternocleidomasteoid in the healthy group was longer than that in the forward head group by 64 ms (P=0.037). Conclusion In sum, these results could be used in rehabilitation protocols for children with forward head posture in clinical settings.